2017
DOI: 10.18203/2320-1770.ijrcog20175857
|View full text |Cite
|
Sign up to set email alerts
|

Need of premarital care

Abstract: Background: Marriage is considered a remarkable event in an individual’s life. It provides people with a sense of belonging, support, security and responsibility. We put so much of efforts to find a good match for our younger and loved ones but we forget to match the most important wealth of our life “Health”. This study aimed to know the knowledge, attitude and practice of the population through a structured questionnaire.Methods: A cross-sectional study was conducted using a self-administered questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
1
1
0
2
Order By: Relevance
“…A person's health behavior is closely related to his knowledge about it [21,22]. In research on the need for premarital care, in the form of premarital health examination services, decisions taken by a person are influenced by the level of knowledge about the impact of the decisions to be taken [23]. This is in line with the results of this study, where there were significant differences in general knowledge of reproduction, sexually transmitted diseases, premarital reproductive health examinations.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A person's health behavior is closely related to his knowledge about it [21,22]. In research on the need for premarital care, in the form of premarital health examination services, decisions taken by a person are influenced by the level of knowledge about the impact of the decisions to be taken [23]. This is in line with the results of this study, where there were significant differences in general knowledge of reproduction, sexually transmitted diseases, premarital reproductive health examinations.…”
Section: Discussionsupporting
confidence: 84%
“…The results showed that there were significant differences in attitudes and behaviors of reproductive health, sexually transmitted diseases, and premarital health checks before and after the intervention video were given. This reflects the importance of reproductive health education in increasing knowledge and attitudes and behavior regarding reproductive health and premarital screening programs [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Sehingga preventif sedari dini sangat dibutuhkan salah satunya dengan melakukan pemeriksaan HIV pranikah untuk calon pengantin agar mengetahui status HIV nya positif atau negatif supaya bisa ditindaklanjuti dan memutuskan rantai penularannya (Bansiwal et al, 2017;Direktorat Promosi Kesehatan & Pemberdayaan Masyarakat, 2018;Ministry of Health -Kingdom of Saudi Arabia, 2019). Semakin terdeteksi secara dini calon pengantin yang positif HIV, maka diharapkan penularan terhadap pasangan atau yang lainnya dapat dicegah dengan mudah serta dilakukan pendampingan untuk pengobatan dan penularannya.. Namun sayangnya, persyaratan melakukan pemeriksaan HIV pranikah ini dilakukan calon pengantin hanya sebagai formalitas untuk melengkapi persyaratan menikah saja.…”
Section: Pendahuluanunclassified
“…Prevalensi stunting lebih tinggi pada anak berusia 2 tahun dan berkurang dengan bertambahnya usia (Bansiwal et al, 2017).…”
unclassified